Features of philosophical worldview in I.P. Shchegolikhin’s essays (Eurasian Journal of Philology Science and Education, 2018)
The article discusses the features of the philosophical worldview in I.P. Shchegolikhin’s essays.Acute social issues, openness and independence of creative citizenship, pioneering quest to image thetruth of life, and complex searches for value in his prose have long attracted researchers of the writer. Onthe example of the works «I do not regret, do not call, do not cry ...» and «Love for another man», is considered the explicitness of the author’s position, I. Shchegolikhin’s essayistic style of writing. It is notedthat in the essays by I. Shchegolikhin important place is taken by the concepts «past» and «memories».The analysis led to the conclusion that the essays of I. Shchegolikhin are characterized by interaction ofphilosophy and literary texts, the transformation of narrative forms, the adjustment position of the authorand the author’s view, the narrator, and the thematic diversity.